Flexural strengthening of one-way reinforced concrete slabs using near surface-mounted BFRP bars - Omar Aljidda (17823488) (2024)
This study examines the flexural behavior of reinforced concrete (RC) one-way slabs strengthened with near-surface mounted (NSM) basalt fiber-reinforced polymer (BFRP) bars. Ten RC slabs were subjected to four-point loading until failure. Various parameters including the steel reinforcement ratio (0.48and 0.95%), the NSM-BFRP reinforcement ratio (0.17, 0.25, and 0.35%), and two types of epoxy adhesives (Sikadur-30 and NSM-Gel) were investigated. The experimental results demonstrated the remarkable efficacy of the NSM-BFRP bars in enhancing the flexural performance of the strengthened slabs, especially those with lower steel reinforcement ratios. Compared to the control slabs, the ultimate loads were increased by 51‐123% and 21‐44% for slabs with 0.48 and 0.95% steel reinforcement ratios, respectively, while the ductility indices were increased by 10‐53% and 29‐79%. The type of the epoxy adhesive used had minimal impact on the flexural behavior of the strengthened slabs. Failure primarily occurred due to steel yielding followed by the rupture of the NSM-BFRP bars or by concrete crushing, depending on the reinforcement ratio provided. The cracking, yield, and ultimate loads of the strengthened slabs were predicted using the formulations of ACI 440.2R [3] guideline. Good agreement between the predicted and the experimental results were obtained, with ACI formulations being on the conservative side. Other Information Published in: Engineering Structures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.engstruct.2024.117507